PENGARUH VARIASI METODE DRYING PROSES TERHADAP KEKERASAN PENGECATAN BODY KENDARAAN BERMOTOR - F. Demmatacco; Hermon. Latumaerissa; J.M Nanulaita (Department of Mechanical Engineering, 2024)
Coating is a process of applying paint in liquid form to an object, to create a thin layer which then forms a hard layer or paint layer. Factors that affect the quality of painting are the materials used, the viscosity of the paint, the painting temperature, and the skill in applying the paint. This study is to observe the process of changing the hardness value on the surface of the paint from coating. The drying process of painting uses 4 forms, namely drying indoors, outdoors, in an oven at a temperature of 50°C and 60°C with a mixture of paint, 100% base: 50% hardener + Thinner (10% of the base) Based on the study of the effect of the paint drying process on the hardness value of the coating, it can be concluded that the results of the average hardness value obtained, namely the use of the drying method using an oven with a temperature of 60°C has the highest hardness value of 84.10 HV followed by 82.90 HV and 81.93 HV for oven drying with a temperature of 50°C and drying indoors with a temperature of 35°C - 36°C, while the lowest hardness value is in outdoor drying with a temperature of 37°C - 39°C with a value of 80.68 HV. Keywords: Hardness Value, Coating, Temperature.